Medical devices used in enteral nutrition - Marta Szumilak; Jacek Owczarek; Katarzyna Nowak (Polish Pharmaceutical Society, 2021)
Medical nutrition therapy refers to the delivery of energy and nitrogen substrates in amounts that meet the current needs of patients who are not able to consume or absorb enough nutrients to sustain adequate nutrition and hydration. Enteral tube feeding is nutrition therapy given via a tube or stoma into the intestinal tract distal to the oral cavity. Essential elements of a properly conducted nutritional intervention are enteral access feeding devices, providing enteral formulas into the patient's intestinal tract. Such products include, among others, feeding sets, enteral syringes, enteral feeding pumps, and enteral feeding tubes (nasogastric tubes, nasojejunal tubes, gastrostomy, jejunostomy). Currently, we are observing a significant development of the enteral feeding devices market. It results from growing requirements for healthcare, the need to improve the patients' quality of life, and the development of new technologies. The rising prevalence of chronic diseases such as diabetes, cancer, gastrointestinal diseases, neurological disorders, the rising number of preterm births, population aging as well as growing awareness of enteral nutrition are no less important. This article reviews the types, features, applications, and contraindications of enteral access feeding devices as well as possible complications of their use. Particular attention is paid to solutions aimed at minimizing the risk of enteral misconnections resulting in serious patient harm and even death due to the unintended administration of enteral formula into the intravascular system. The main changes in the legal regulations on medical devices resulting from the entry into force of Regulation (EU) 2017/745 of the European Parliament and of the Council of 5 April 2017 on medical devices, amending Directive 2001/83/EC, and Regulation (EC) No 178/2002 and Regulation (EC) No 1223/2009 and repealing Council Directives 90/385/EEC and 93/42/EEC) - MDR (Medical Device Regulation) were also presented.